ANALISIS FAKTOR RISIKO PELAKSANAAN PEMBERANTASAN SARANG NYAMUK DEMAM BERDARAH DENGUE (PSN-DBD) SELAMA PANDEMI COVID-19 DI WILAYAH DESA CATURTUNGGAL DEPOK SLEMAN - Tri Wahyuni Sukesi; Vicky Dita Ambarwati (Universitas Ahmad Dahlan, 2022)
DHF is still a health problem in the Special Region of Yogyakarta as evidenced by an increase in the CFR rate in 2019 by 0.2%, increasing to 0.4% in 2020. The incidence rate of DHF in Sleman Regency in 2019 was 67.97%. This figure still exceeds the indicators for the strategic plan of the Ministry of Health of the Republic of Indonesia. In addition, the COVID-19 pandemic since 2019 has also demanded the government and the public to be able to adapt to the new-normal as it is today, especially with regulations restricting activities outside the home to break the chain of transmission of COVID-19. During a pandemic like today, apart from the high number of COVID-19 cases, the government is still faced with other health problems, namely the high number of dengue case. The type of research used in this research is quantitative method using a cross sectional research design. The results of the study explained that there was no relationship between knowledge and behavior of PSN-DHF during the COVID-19 pandemic in Santren Hamlet, Caturtunggal Village, Depok Sleman with a p value of 1,000 (p > 0.05). There is no relationship between attitude and PSN-DHF behavior during the COVID-19 pandemic in Santren Hamlet, Caturtunggal Village, Depok Sleman with a p value of 1,000 (p > 0.05). There is no relationship between work activity and PSN-DHF behavior during the COVID-19 pandemic in Santren Hamlet, Caturtunggal Village, Depok Sleman with a p value of 0.872 (p > 0.05). There is no relationship between knowledge and behavior, there is no relationship between attitude and behavior, there is no relationship between work activities and PSN-DHF behavior during the COVID-19 pandemic in Santren Hamlet, Caturtunggal Village, Depok Sleman.